2016
DOI: 10.1111/zph.12271
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Severe Acute Respiratory Syndrome‐Related Coronavirus and Alphacoronavirus in the Bat Population of Taiwan

Abstract: Bats have been demonstrated to be natural reservoirs of severe acute respiratory syndrome coronavirus (SARS CoV) and Middle East respiratory syndrome (MERS) CoV. Faecal samples from 248 individuals of 20 bat species were tested for partial RNA-dependent RNA polymerase gene of CoV and 57 faecal samples from eight bat species were tested positive. The highest detection rate of 44% for Scotophilus kuhlii, followed by 30% for Rhinolophus monoceros. Significantly higher detection rates of coronaviral RNA were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…Notably, this may be of public health concern, as both species are in close proximity to human beings: Fringed long‐footed Myotis ( M. fimbriatus ) was collected from a city sewer, and Common Serotine ( E. serotinus ) was captured from rural homes. Despite previous reports of SARS‐like coronaviruses in Rhinolophus bats in China (Chen et al., ; He et al., ; Li et al., ), no SARS‐like coronaviruses were detected in Rhinolophus bats in this study, which may be due to the limited sample size of Rhinolophus bats.…”
Section: Discussioncontrasting
confidence: 96%
“…Notably, this may be of public health concern, as both species are in close proximity to human beings: Fringed long‐footed Myotis ( M. fimbriatus ) was collected from a city sewer, and Common Serotine ( E. serotinus ) was captured from rural homes. Despite previous reports of SARS‐like coronaviruses in Rhinolophus bats in China (Chen et al., ; He et al., ; Li et al., ), no SARS‐like coronaviruses were detected in Rhinolophus bats in this study, which may be due to the limited sample size of Rhinolophus bats.…”
Section: Discussioncontrasting
confidence: 96%
“…During 2016-2017, a putative new lyssavirus was found in the Japanese pipistrelle bat in the same country (Hu et al, 2018). SARS-related coronavirus and Alphacoronavirus were also detected in the country's bat population (Chen et al, 2016). To obtain more information on bat-derived pathogenic viruses in East Asia, this study aimed to determine the viruses present in fecal guano of Taiwanese insectivorous bats caves.…”
Section: Introductionmentioning
confidence: 99%
“…Both MERS-CoV and bat CoV-HKU4 can use bat and human DPP4 to infect cells originating from humans, camels, bats, and other animal species [12,13] and HCoV-NL63 can replicate in the lung cell line from tricolored bats [8].Little information is available regarding cross-species events for animal CoVs. A previous study detected Scotophilus bat CoV-512 in four different bat species along with Miniopterus bat CoV-1A and Rhinolophus SARS-related CoV in Taiwan through the reverse transcription polymerase chain reaction (RT-PCR) [14]. Antibodies specific to the nucleocapsid (N) protein fragments of Scotophilus bat CoV-512 were detected in serum collected from three bat species, namely Scotophilus kuhlii, Miniopterus fuliginosus, and Rhinolophus monoceros [15].…”
mentioning
confidence: 99%
“…Antibodies specific to the nucleocapsid (N) protein fragments of Scotophilus bat CoV-512 were detected in serum collected from three bat species, namely Scotophilus kuhlii, Miniopterus fuliginosus, and Rhinolophus monoceros [15]. A close relationship and possible gene recombinants between Scotophilus bat CoV-512 and PEDV were observed through sequence alignments [14,16]. The results of the cell entry assay also indicated that PEDV can infect cells originating from pigs (PK15 and ST), humans (Huh-7 and MRC5), monkeys (Vero) and Tadarida brasiliensis bats (Tb1-Lu) [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation